2017
DOI: 10.1111/jgs.15073
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor Use and Dementia Risk: Prospective Population‐Based Study

Abstract: OBJECTIVES: To determine whether higher cumulative proton pump inhibitor (PPI) exposure is associated with greater dementia risk. DESIGN: Prospective population-based cohort study. SETTING: Kaiser Permanente Washington, an integrated healthcare delivery system in Seattle, Washington. PARTICIPANTS: Individuals aged 65 and older without dementia at study entry (N = 3,484). MEASUREMENTS: Participants were screened for dementia every 2 years, and those who screened positive underwent extensive evaluation. Dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 41 publications
4
61
0
4
Order By: Relevance
“…To the Editor: Liao and colleagues 1 report that proton pump inhibitors (PPIs) do not increase the risk of Alzheimer's disease (AD) in older adults, using a case-control series from the Taiwan National Health Insurance database. These findings replicate the conclusions of our study 2 and that of Gray and colleagues, 3 but other studies, 4,5 including another case-control report 6 also in Taiwan using the national database, indicate that PPIs confer a greater risk of developing dementia and AD.…”
Section: Reply To: Association Between Proton Pump Inhibitors and Alzsupporting
confidence: 91%
See 1 more Smart Citation
“…To the Editor: Liao and colleagues 1 report that proton pump inhibitors (PPIs) do not increase the risk of Alzheimer's disease (AD) in older adults, using a case-control series from the Taiwan National Health Insurance database. These findings replicate the conclusions of our study 2 and that of Gray and colleagues, 3 but other studies, 4,5 including another case-control report 6 also in Taiwan using the national database, indicate that PPIs confer a greater risk of developing dementia and AD.…”
Section: Reply To: Association Between Proton Pump Inhibitors and Alzsupporting
confidence: 91%
“…This is reminiscent of how, several years ago, AEDs were blamed as a cause of an increase in the risk of suicide (Food and Drug Administration warning in January 2008), a claim that many studies have subsequently questioned or minimized. 3 Misinterpretations of the suggested association can have serious consequences by undermining physicians' confidence in prescribing necessary medications and lead to poor adherence, with potential life-threatening consequences.…”
Section: No Evidence Of a Causal Role Of Antiepileptic Drug Treatmentmentioning
confidence: 99%
“…This was the same conclusion as other large studies [3]. However, recently, Gray et al [4] reported that PPI use is not associated with dementia risk, even for people with high cumulative exposure in a prospective population-based study. A prescription sequence symmetry analysis conducted by Park et al [5] also indicated that the risk of PPIs being associated with dementia may be overestimated.…”
supporting
confidence: 70%
“…There is a well-recognized epidemiological link between PPIs and the increased risk of dementia [2, 3]. However, many studies have reported that PPIs are not associated with a greater risk of dementia or AD [4, 5]. But the evidence for this is limited.…”
mentioning
confidence: 92%
“…Regarding the dementia risk, initially, three cohort studies Haenisch et al, 2015;Tai et al, 2017) and one crosssectional study (Herghelegiu, Prada, & Nacu, 2016) found a positive association between dementia risk and PPI use. However, this association was not found in more recent studies, including a case control study (Imfeld, Bodmer, Jick, & Meier, 2018) and a cohort study (Gray et al, 2018). One cross-sectional study (de Souto Barreto et al, 2013) and one case control study (Booker, Jacob, Rapp, Bohlken, & Kostev, 2016) even found a decreased risk of dementia with PPI use.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 85%